Government supervision on quality of smoking-cessation counselling in midwifery practices: a qualitative exploration - Sandra F. Oude Wesselink; Annemiek Stoopendaal; Vicki Erasmus; Déan Smits; Johan P. Mackenbach; Hester F. Lingsma; Paul B. M. Robben (BMC, 2017)
Abstract Background The Dutch Healthcare Inspectorate supervises care providers in order to improve quality of care. Recently the inspectorate assessed and promoted the use of a guideline on smoking-cessation counselling in midwifery practices. The supervision programme consisted of an announcement of the enforcement deadline for the guideline and site visits. The purpose of our qualitative study was to identify factors related to guideline adherence after the supervision programme, and investigate whether the programme had helped improve adherence. Methods We conducted semi-structured interviews with inspected and non-inspected midwives. Additionally, we studied documents and observed the inspection process. The sampled midwives all work in primary care midwifery practices providing care to pregnant smokers. The questions included the current provision of smoking-cessation counselling, support to the midwife in counselling, recent changes in provision of counselling, reasons for recent changes, knowledge about the supervision programme, and experiences with supervision by the inspectorate. Results Our results show that guideline adherence depends on several factors. Awareness and familiarity with the guideline are important, as is outcome expectancy. Additionally, motivation, guideline factors and environment factors were mentioned. Besides these previously documented factors, we found that professional collaboration also determined guideline adherence. Increased collaboration in counselling is associated with greater adherence to the guideline, such as provision of counselling and taking required training. The supervision programme helped improve stop-smoking counselling, by making midwives aware of the counselling and giving them an extrinsic motivation to provide counselling. Conclusion Motivation and environmental aspects were the most important factors related to guideline adherence, and professional environment was added as significant factor. The improved guideline adherence is partly attributable to the supervision programme.